An analytical study of current-voltage characteristics and breakdown performance of GaInP∕GaAs composite collector double heterojunction bipolar transistor - Goh, Y. L.; Ong, D. S.; Yow, H. K. (2004)
An analytical model taking into account the nonlocal dead-space effects is developed to study the dc characteristics and avalanche multiplication of GaInP/GaAs double heterojunction bipolar transistor (DHBT) incorporating composite collector designs. The dependence of the turn-on characteristics and the multiplication onset of the HBT on the device composite layer thickness and doping densities are investigated. In this paper, optimum combinations of composite parameters are presented to obtain zero spike effect in the base-collector heterojunction conduction band and to improve output breakdown voltages. The model is then applied to the GaInP/GaAs DHBT with AlGaAs in the composite collector, which is found to have good I-V characteristics and high operating voltage range before the onset of avalanche multiplication. (C) 2004 American Institute of Physics.